Pengembangan Media E-Flashcard sebagai Media Pembelajaran Bahasa Indonesia Kelas I Sekolah Dasar - Anna Desfrida; Fahrurrozi Fahrurrozi; Prayuningtyas Angger Wardhani (Universitas Indraprasta PGRI Jakarta, 2023)
Challenges in learning language skills are still often found in Indonesian elementary schools. This affects children's ability to understand the information needed in the knowledge transfer process. One of the reasons is the use of learning media that does not look attractive. Referring to existing problems, the aim of this research is to develop learning media in the form of electronic flashcards and test its suitability as a medium for learning Indonesian for Class I Khairul Uswah Private Elementary School which focuses on reading skills. This research was conducted in 2023. The method used is the Research and Development (RnD) method by utilizing the 4D approach model and using a validity test consisting of two validity tests, namely a validity test by media experts and also a validity test by language experts. using a questionnaire instrument with a Likert scale. The results were in the form of a percentage value of 92.5% for the linguist validity test and 93.3% for the media expert validity test, as well as a value obtained in the presentation of 92.9% for the combined score which was included in the category Very good. This means that the E-flashcard learning media is suitable and can be used as a medium for learning Indonesian for Class I Elementary School.